## Solving the Equation: 0.3(x-2) = 0.6 + 0.2(x+4)

This article will guide you through solving the linear equation **0.3(x-2) = 0.6 + 0.2(x+4)**.

### Step 1: Distribute

Begin by distributing the coefficients on both sides of the equation:

**Left side:**0.3(x-2) = 0.3x - 0.6**Right side:**0.6 + 0.2(x+4) = 0.6 + 0.2x + 0.8

The equation now becomes: **0.3x - 0.6 = 0.6 + 0.2x + 0.8**

### Step 2: Combine Like Terms

Combine the constant terms on the right side of the equation:

**0.3x - 0.6 = 1.4 + 0.2x**

### Step 3: Isolate the x Term

Subtract **0.2x** from both sides of the equation:

**0.1x - 0.6 = 1.4**

### Step 4: Isolate x

Add **0.6** to both sides of the equation:

**0.1x = 2**

### Step 5: Solve for x

Finally, divide both sides by **0.1** to isolate **x**:

**x = 20**

### Solution

Therefore, the solution to the equation **0.3(x-2) = 0.6 + 0.2(x+4)** is **x = 20**.